Comportamiento priccional y desgaste Zr-Lv - Fernández, Hipólito Alejo; Ruzzante, José Evaristo; Vosen, J. H. (Comisión Nacional de Energía Atómica; Argentina, 1984)
Fil: Fernández, Hipólito Alejo Comisión Nacional de Energía Atómica; Argentina